The Use of Digital Annotation Tools in Improving Online Public Health Literacy among Youths - Ruhil Amal, Azmuddin; Tuti Ningseh, Mohd Dom; Haslina, Rani; Anis Nadiah, Che Abdul Rahman; Afendi, Hamat (UKM Press, 2023)
Understanding public health materials is important to enhance public health literacy, as the lack of comprehension can have negative repercussions for individuals, society, and the healthcare system. It is essential for youths to grasp fundamental health information because it equips them with the knowledge and ability to address the intricate health needs and challenges of modern society. This study was conducted to assess the reading comprehension ability of youths when engaging with online public health materials in English, with a particular focus on diabetes. For this purpose, the research utilised Digital Annotation Tools (DAT) within an online reading system named Interactive Reading for Academic Disciplines (iREAD). Data were collected from a purposive sample of 30 students enrolled at a Malaysian public university. The students read 12 newspaper articles over the course of four weeks. Content analysis was conducted to analyse the annotations made by students while reading the articles. Both quantitative and qualitative approaches were employed to analyse the data. Analyses of the annotations indicate that students were able to paraphrase, summarise, synthesise, and contextualise ideas while engaging with the articles. The findings revealed that DAT has the potential to improve the understanding of online diabetes health education materials. This is a crucial development towards the increase in health knowledge and literacy as enhanced comprehension may, in turn, lead to increased health knowledge and empower individuals to make informed decisions about their health and well-being, ultimately contributing to higher levels of health literacy.